The role of ICT and financial development on CO₂ emissions and economic growth - Ibrahim Dolapo Raheem; Aviral Kumar Tiwari; Daniel Balsalobre-lorente (African Governance and Development Institute (AGDI), 2019)
This study explores the role of the information and communication Technology (ICT) and financial development (FD) on both carbon emissions and economic growth for the G7 countries for the period 1990-2014. Using PMG, we found that ICT has a long run positive effect on emissions, while FD is a weak determinant. The interactive term between the ICT and FD produces negative coefficients. Also, both variables are found to impact negatively on economic growth. However, their interactions show they have mixed effects on economic growth (i.e., positive in the short-run and negative in the long-run). Policy implications were designed based on these results.
Keywords: E23; F21; F30; O16; 330; ICT; Financial development; Carbon emissions; Economic growth and G7 countries